Pengaruh Penggunaan Model Pembelajaran Kooperatif Tipe Snowball Throwing Terhadap Motivasi dan Hasil Belajar Siswa - Yani Mulyani; Yudi Hidayat; Yayat Hidayat; Mohamad Yudiyanto (Peneliti.net, 2022)
Based on the results of observations, there are several problems, namely the selection of methods that are less varied, student motivation is very lacking and student learning outcomes are less than optimal. This study aims to determine the level of motivation, results, and differences between the two of students' learning by applying the snowball throwing type of cooperative learning model compared to the control class using conventional learning models. This research is included in a population study that uses a sample with data collection techniques: test and non-test. The results showed that (1) there was a better effect on students' learning motivation by applying the snowball throwing type of cooperative learning model compared to conventional learning models; (2) there is a better effect on student learning outcomes by applying the snowball throwing type of cooperative learning model compared to conventional learning models; (3) there is a significant difference in the results of the analysis of students' motivation and learning outcomes, there is a better influence on the motivation and learning outcomes of experimental class students.